Econometric Analysis of the Influence of Microbiological Preparations on the Crop Yield of Dry Mass of Feed Mix - O. A. Shikhova (Статистика и экономика)
The use of statistical methods and econometric modeling has its own specifics when analyzing data obtained from agrobiological studies. When studying such an index as crop yield and selecting factors that influence it, the analyst faces the problem of the need to include explanatory variables in the regression model that have a nonquantitative form of expression, associated with the use of various microbiological preparations for seed treatment. Such a problem can be solved by using dummy variables in the models.The purpose of the research – development of methodological approaches to constructing a regression multifactorial model, including both quantitative and qualitative explanatory variables, describing quantitatively the dependence of the feed mix yield for cows on these factors.Materials and methods. The methodology for solving this research problem is based on fundamental approaches published in scientific papers by scientists covering the problems of using econometric models with dummy variables. The basis of the study is an integrated approach to the use of mathematical and statistical methods for analyzing dependencies between variables, modeling and forecasting, as well as experimental results of studying the level of dry mass yield of the feed mix depending on the nitrogen content in the soil and the use of microbiological preparations “Bisolbi-T” and “Extrasol”, obtained for four mowings carried out in the summer period of 2023.Results. The study and quantitative description of the effect of microbiological preparations “Bisolbi-T” and “Extrasol” at different concentrations of nitrogen in the soil on the yield of dry mass of the feed mix allowed us to obtain econometric two-factor models, in which the factor - the use of the preparation for preliminary treatment of seed material, was included as a dummy variable. Based on the statistically significant regression models obtained during the study, taking into account the periods and cycles of mowing the feed mix, the expected values of its yield at the standard concentration of nitrogen in the soil were calculated, a comparative assessment of the effectiveness of the studied preparations was performed.Conclusion. The use of statistical data analysis methods with the construction of regression models in agrobiological research has certain specifics. The possibility of including dummy explanatory variables in the regression model allows us to study and quantify the impact of nonquantitative factors on crop yields. Obtaining statistically significant models is the basis for forecasting the yield level and making decisions when choosing optimal options for applying fertilizer concentrations, determining preferences for microbiological additives used to increase crop productivity, calculating prospective values of the yield of the feed mix depending on the period of its mowing. All this is of strategic importance when planning the volumes of feed production for farm animals and the amount of expenses of enterprises for their activities, in particular for drawing up a budget for feed costs.